2021
DOI: 10.3934/publichealth.2022008
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff fatigue and burnout during the COVID-19 pandemic in Greece

Abstract: <abstract><sec> <title>Introduction</title> <p>The coronavirus pandemic (COVID-19) is an unprecedented global health crisis with emotional and physical impact on health care workers.</p> </sec><sec> <title>Objective</title> <p>The purpose of this study was to investigate the levels of fatigue and burnout in nursing staff during the pandemic.</p> </sec><sec> <title>Methods</title> <p>The present study involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
3
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 39 publications
6
41
3
4
Order By: Relevance
“…In our sample the female population is significantly younger than males, possibly explaining, in part, the difference in SOC scores, assuming age serves as a confounding variable. Furthermore, research argue that men and women are differentially affected by stressors and make different use of their coping resources [ 40 ].These findings are consistent with reviews and meta-analyses indicating that female nurses are more vulnerable to adverse mental health effects; facts that should be taken into consideration in further research on stress, coping, and health [ 4 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our sample the female population is significantly younger than males, possibly explaining, in part, the difference in SOC scores, assuming age serves as a confounding variable. Furthermore, research argue that men and women are differentially affected by stressors and make different use of their coping resources [ 40 ].These findings are consistent with reviews and meta-analyses indicating that female nurses are more vulnerable to adverse mental health effects; facts that should be taken into consideration in further research on stress, coping, and health [ 4 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…High rates of burnout and depression in health care workers are a consistent finding in studies worldwide even before COVID-19 [ 28 , 43 , 44 ]; the pandemic crisis has highlighted the problem. The increase in burnout may be due to the high pressure exerted on hospitals by the pandemic [ 4 ]. At the time of the study, cases and admissions to Greek hospitals were on the rise, while work leave for healthcare staff had been suspended for the preceding five months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long working hours and work overload, exposure to infection and close contact with COVID-19 patients, the stigma of being a potential carrier of the infection, social media pressures, and increase in the number of death cases lead to fatigue, despair, and helplessness in the nurses and undermine the quality and quantity of nursing care [ 12 ]. Other consequences of job fatigue in nurses are absence, delay, job burnout, and concentration disorders, with adverse effects on patient safety [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 46.7% of the participants feared that they might be carriers of COVID-19 and 38.9% feared COVID-19 infection [ 27 ]. In a study by Sikaras et al, 52.4% of the respondents worked in COVID-19 units, the results of 67.9% and 42.9%, respectively, suggested the occurrence of fatigue and burnout among them and showed a strong positive correlation ( p < 0.01, r = 0.70) [ 28 ]. The findings of Alameddine et al showed that 67.8% of the nurses were satisfied with their jobs and most of the nurses stated that they were unlikely to quit their jobs in the coming year (76.2%).…”
Section: Discussionmentioning
confidence: 99%